2020
DOI: 10.7498/aps.69.20201167
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional numerical study of effect of magnetic field on laser-driven Kelvin-Helmholtz instability

Abstract: Kelvin-Helmholtz instability is the basic physical process of fluids and plasmas. It is widely present in natural, astrophysical, and high energy density physical phenomena. With the construction of strong laser facilities, the research on high energy density physics has gained new impetus. However, in recent years the magnetized Kelvin-Helmholtz instability was rarely studied experimentally. In this work, we propose a new experimental scheme, in which a long-pulsed nanosecond laser beam is generated by a dome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
2
0
1
Order By: Relevance
“…The multimode sinusoidal disturbance is introduced between the ch and foam layers. The simulation in this paper includes four cases, as shown in Table 1 Based on our previous work 4,7 , the results show that the Biermann self-generated magnetic field does not change the interface dynamics of RTI, and all simulation cases involved in this paper ignore the Biermann self-generated magnetic field effect.…”
Section: Theoretical Simulation Modelmentioning
confidence: 97%
See 1 more Smart Citation
“…The multimode sinusoidal disturbance is introduced between the ch and foam layers. The simulation in this paper includes four cases, as shown in Table 1 Based on our previous work 4,7 , the results show that the Biermann self-generated magnetic field does not change the interface dynamics of RTI, and all simulation cases involved in this paper ignore the Biermann self-generated magnetic field effect.…”
Section: Theoretical Simulation Modelmentioning
confidence: 97%
“…In the engineering field, such as the research of inertial confinement fusion (ICF), it has been found that due to the existence of RTI and Kelvin Helmholtz instability, the target implosion process will be seriously affected, resulting in material mixing and energy dissipation between different fuel layers, and damaging the high compression implosion performance. It is one of the critical factors for ignition failure 6,7 .…”
Section: Introductionmentioning
confidence: 99%
“…•A ‚[z£AMR¤õU, ±9E, ^6NÄåAE£MHD¤)Žì, Óž|±-1 ‚Jl!Ë * Ñ. Ù¥ n §ÝË MHD)Žì£3T¤OE±OŽ-1UþoeÈ!õ|Ë *Ñ!²ï>f!lfÚË §Ý, cÙ•^u [-1°Ä HEDP¢ , •)^z 6!MHDØ-½5 [12,23] . [¥ 9 q G • §ÚØß²ÝLÄuIONMIX4ê⥠[24] .…”
Section: Nø [ ú¢ •Yunclassified